Peukert Generalized Equations Applicability with Due Consideration of Internal Resistance of Automotive-grade Lithium-ion Batteries for their Capacity Evaluation - Nataliya N. Yazvinskaya; Mikhail S. Lipkin; Nikolay E. Galushkin; Dmitriy N. Galushkin (Recent Progress in Science and Technology Vol. 6, 2023)
In this paper, the applicability of the Peukert equation and its generalizations was investigated for capacity evaluation of the automotive-grade lithium-ion batteries. It is proved that the classical Peukert equation is applicable within the range of the discharge currents from 0.2Cn to 2Cn (Cn is the nominal battery capacity). As a rule, the operating currents of many automotive-grade lithium-ion batteries are exactly within this range of the discharge currents. That is why, successfully, the classical Peukert equation is used in many analytical models developed for these batteries. The generalized Peukert equation C = Cm/(1+(i/i0)n) is applicable within the discharge currents range from zero to approximately 10Cn. All kinds of the operating discharge currents (including both very small ones and powerful short-term bursts) fall into this discharge currents range. The modified Peukert equation C = Cm(1-i/i1)/((1-i/i1)+(i/i0)n) is applicable at any discharge currents. This equation takes into account the batteries’ internal resistance and has the smallest error of the experimental data approximation. That is why the discussed modified Peukert equation is most preferable for use in analytical models of the automotive-grade lithium-ion batteries. The paper shows that all the parameters of the generalized Peukert equations have the clear electrochemical meaning in contrast to the classical Peukert equation, where all the parameters are just empirical constants.